2021
DOI: 10.30607/kvj.913058
|View full text |Cite
|
Sign up to set email alerts
|

Somatik Hücre Sayısının ve Mevsimin Manda Süt Kalitesine Etkisinin Araştırılması

Abstract: The somatic cell count (SCC), chemical composition and microbiological quality of milk are the most important features in terms of overall quality of raw milk. In our study, the seasonal SCC, chemical composition and microbiological qualities of the milk obtained were measured, and the seasonal effect on these parameters was investigated. In terms of SCC, the maximum value of the summer sample was the highest with 465000 units/ml (average 233500 units/ml), while in terms of microbiological criteria, the total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 15 publications
3
2
0
Order By: Relevance
“…The fat amount in the sample OR2 was statistically different (P<0.05) from the others (P<0.05). Similar fat amounts were found for the buffalo milk samples (Varricchio et al 2007, Han et al 2012, Kashwa 2016, Çinar et al 2019, Gürler et al 2021. The results show that, the fat amount in the samples other than the sample OR2, are in agreement with the reported literature.…”
Section: Physicochemical Compositions Of Buffalo Milk Samplessupporting
confidence: 89%
See 4 more Smart Citations
“…The fat amount in the sample OR2 was statistically different (P<0.05) from the others (P<0.05). Similar fat amounts were found for the buffalo milk samples (Varricchio et al 2007, Han et al 2012, Kashwa 2016, Çinar et al 2019, Gürler et al 2021. The results show that, the fat amount in the samples other than the sample OR2, are in agreement with the reported literature.…”
Section: Physicochemical Compositions Of Buffalo Milk Samplessupporting
confidence: 89%
“…Among all samples, the OR4 had the lowest amount of non-fat dry matter (6.73%), followed by the OR2 (8.86%) and the highest value was found in the OR1 (9.82%). In the current study, the amount of non-fat dry matter of the sample OR4 was found to be lower than reported values of Çinar et al (2019) and Gürler et al (2021), while the others were compatible with the literature.…”
Section: Physicochemical Compositions Of Buffalo Milk Samplessupporting
confidence: 89%
See 3 more Smart Citations